1998
DOI: 10.1002/(sici)1521-3765(19980210)4:2<260::aid-chem260>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Anthryloligothienylporphyrins: Energy Transfer and Light-Harvesting Systems

Abstract: In this paper we report on the synthesis and photophysical properties of the energy-transfer system 2 a, in which a quinquethiophene bridge is terminally linked to the 5-position of a porphyrin and to the 9-position of an anthracene group. The photoexcitedstate properties were studied by steady-state fluorescence and picosecond time-resolved fluorescence measurements as well as fluorescence excitation spectroscopy. The weak electronic interaction of the subunits anthracene, quinquethiophene and porphyrin resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(59 citation statements)
references
References 9 publications
(24 reference statements)
0
57
0
2
Order By: Relevance
“…The linear D-A triad 2.226 was also prepared by condensation of aldehyde 2.224 with pyrrole and hexanal in a yield of 3% which had to be separated from other possible isomers (Chart 2.37). 318 Steadystate fluorescence and picosecond time-resolved fluorescence measurements revealed that selective excitation of the anthracene donor (254 nm) leads to an efficient unidirectional intramolecular energy transfer to the emitting porphyrin (650-800 nm) Via the oligothiophene bridges.…”
Section: Porphyrin-functionalized Oligothiophenesmentioning
confidence: 85%
See 1 more Smart Citation
“…The linear D-A triad 2.226 was also prepared by condensation of aldehyde 2.224 with pyrrole and hexanal in a yield of 3% which had to be separated from other possible isomers (Chart 2.37). 318 Steadystate fluorescence and picosecond time-resolved fluorescence measurements revealed that selective excitation of the anthracene donor (254 nm) leads to an efficient unidirectional intramolecular energy transfer to the emitting porphyrin (650-800 nm) Via the oligothiophene bridges.…”
Section: Porphyrin-functionalized Oligothiophenesmentioning
confidence: 85%
“…318 Cross-coupling reactions of 5,5′-dibromoterthiophene with the Grignard reagent of 2-bromo-3-pentylthiophene yielded quinquethiophene 2.222. Lithiation of the resulting quinquethiophene followed by reaction with anthrone gave 9-anthryl-substituted dipentylquinquethiophene 2.223.…”
Section: Porphyrin-functionalized Oligothiophenesmentioning
confidence: 99%
“…Furthermore, oligomeric [10,11] and polymeric [12] meso-tetrakis-thiophene porphyrin films have shown promising properties as robust catalysts for the oxidation of organic substrates [13,14]. Despite this, and the importance of intermolecular interactions in many applications, there are only three reported Xray structures of thiophene-substituted porphyrins [15][16][17].…”
Section: Introductionmentioning
confidence: 93%
“…27). 60 In another example, Ziessel et al reported a multichromophoric array 34 in which BODIPY dyes having different emission properties are organized around a truxene core (Fig. 28).…”
Section: Brief History and Design Strategymentioning
confidence: 99%